(untitled) (Research, Society and Development, 2022)
It is possible to affirm that the cancer associated with its treatment can lead to vulnerabilities and changes in the elderly’s cognition state, hindering their recovery process. Therefore, it is necessary to identify vulnerability and cognitive status in the clinical environment, in order to generate benefits to them. Objective: The aim of this study was to identify whether elderly cancer patients have a lower sense of coherence and greater vulnerability when analyzed using the Sense of Coherence (SOC-13) and Functional Clinical Vulnerability Index (IVCF-20) instruments and to evaluate the relationships between the results of these instruments with the epidemiological and clinical characteristics of the patients. Methodology: The sample consisted of 32 elderly cancer patients and the research consisted of a prospective observational cross-sectional study. Results: It can be said that less coherent, older patients with lower family income and longer disease duration are considered more vulnerable. Conclusion: The importance of assessing cognition and vulnerability in these patients is perceived, as the professional will be able to implement actions and strategies to reduce the risk of vulnerability and improve the cognition status of patients.